PDI Perjuangan Evaluation: Between Party Identity vis à vis Mass Base Expansion - Pradita, Maurit Putera; Nurhandjati, Nurul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This journal article reflects on the results of the Indonesian Democratic Party of Struggle (PDI-P) legislative elections, which left several important notes, particularly regarding the party's weaknesses in the religious sphere. Negative sentiment about religion still clings to the party despite its three consecutive victories in the 2014, 2019, and 2024 legislative elections. In an ideological context, PDI-P has consistently maintained and upheld its ideology, even in unfavorable situations. However, on the other hand, PDI-P is faced with a party image that is not as good as its vote acquisition, as well as political attitudes, party policies, and political communication that still need improvement. Using qualitative research methods, the findings and results of the study indicate that PDI-P can maintain its ideology by limiting its reach to a segment of conservative Muslim voters or try to move towards the center and expand its mass base to all sectors, at the risk of sacrificing the ideology they have long adhered to.